Socio-Economic and Demographic Study in Majhi Community - Bimali, Ganesh (Rupantaran: A Multidisciplinary Journal, 2020)
Majhi community is completely soc- economically backward community. This article is focused on social-economic and demographic study in Majhi. The sample size is selected all (41) HHs of study area (ward no 4 and 5 of Aatharai Rural Municipality) by using census sampling. Both primary and secondary sources have been used. The open ended and closed ended questionnaire were designed to complete this study. The collected information were analyzed and interpreted with quantitative way by mean, ratio and percentage using SPSS (Statistical package for social science). The data were collected through head of household or responsible person of household. The Majhi people of study area have poor educational status, they changed their occupation boating, fishing to agriculture, foreign employment which changed their income level. Demographically, the numbers of female are more than male; life expectancy is very low due to few number of age over 60 and high number of less than age 15 population. The study help to find the real socio- economic and regional situation of Majhi people in regional or of specific area.